DINAMIKA WACANA FORMALISASI SYARIAT DALAM POLITIK: IKHTIAR MENEMUKAN RELEVANSI RELASI AGAMA DAN NEGARA PERSPEKTIF INDONESIA - Mahathir Muhammad Iqbal (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This research is an effort to find the relevance of the relationship between religion and the state are ideal. Because the formalization of Islamic shariah issue in political discourse is an interesting study in the relation between religion and state. By using the library approach, this article analyzes the involvement of the state in regulating citizens to implement Islamic shariah in Indonesia. Neutrality of the state to be the key in finding the relationship of both. Theoretically, this study provides an explanation that neutrality is not only understood as a state of devotion to give the rights of citizens to pray by faith, but also to limit citizens. For the implementation of shariah will be established and run well, when the state has a neutrality. So the state does not attract Islamic shariah becomes an official policy or state laws (shariah formalization). So also a Muslim can bring religion into the political circle, but only in the level of political ethics.